OPTIMALISASI PENERAPAN PERMIT TO WORK GUNA MEMASTIKAN KESELAMATAN DI ATAS KAPAL MV. MEDELIN FIRST - Ardiansyah, Ferry; Imam Firdaus, Muhamad; Rahmawati, Maulidiah; Sutoyo, Sutoyo (Penerbit Lafadz Jaya, 2026)
Work safety aboard merchant ships remains critical as occupational accidents frequently occur due to inadequate implementation of safety procedures. This study aims to identify the factors causing the suboptimal application of the Permit to Work (PTW) system on board MV. Medelin First, analyze its impact on safety, and formulate optimization strategies. A qualitative descriptive method was employed with purposive and snowball sampling involving 5–7 ship crew members as participants. Data were collected through semi-structured interviews, direct observations, and document analysis, and analyzed using the Miles and Huberman interactive model. Results show that PTW documents were formally prepared but not consistently implemented in practice, particularly in gas testing, supervision, and personal protective equipment usage. The findings indicate that these inconsistencies elevate accident risks during high-risk tasks such as hot work and enclosed space entry. The conclusion emphasizes that PTW optimization requires strict supervision, adequate safety equipment, integrated risk assessment, and regular safety training to build an effective safety culture on board.